Membangun Komunikasi yang Komunikatif - Erwan Efendi; Nirwana Amaliah Pulungan; Putri Apriliani; Pradana Aria Dewangga (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Communicative communication is a process when a person or several people provide information to connect with the other person or the communicator using language, attitudes or behavior that is easily understood by the communicator. Communicative communication is a process when a person or several people provide information to connect with the other person or the communicator using language, attitudes or behavior that is easily understood by the communicator. In all situations this communicative attitude is needed to facilitate communication with other people, understand things and so on. And we must apply this communicative attitude from an early age so that we can train someone to have the courage to speak in public, to express opinions and to make decisions. Of course, we have to study communicative attitudes first, starting from understanding to example sentences. Because this can make it easier when communicating with other people. Communicative when communication takes place on the individuals who are involved and want to make the interlocutor understand his intentions by trying to achieve what is called validity claims. Hardiman (2009) mentions 4 kinds of claims. And any effective communication must also achieve this fourth claim and the person who is able to communicate. keywords: communication, communicative